Superplastic Forming of Zr-Based Bulk Metallic Glasses - Xiangyun Zhang; Chenkai Zhao; Caiyun Xiao; Zizhou Yuan; Jiankang Huang (Metals, 2023)
In this paper, the partially crystallized Zr70Cu13.5Ni8.5Al8 bulk metallic glasses (BMGs) were prepared, and their superplastic deformation ability in the supercooled liquid region was studied via compression over a wide range of strain rates from 5 × 10−4 s−1 to 1 × 10−2 s−1. It has been found that the superplastic deformation behavior of the BMGs is strongly dependent on the strain rate and temperature. The flow behavior of the BMGs transformed from Newtonian fluid to non-Newtonian fluid with the increase in the strain rate and the decrease in temperature. Based on the high-temperature compression results, a thermalplastic forming map was constructed, and the optimal superplastic forming parameters were obtained. Then, gears were successfully extruded using part of the optimal thermal processing parameters. Further studies showed that high-temperature extrusion induced the crystallization of the BMGs, which increased the microhardness of the gears.